EPC-Derived Exosomal miR-1246 and miR-1290 Regulate Phenotypic Changes of Fibroblasts to Endothelial Cells to Exert Protective Effects on Myocardial Infarction by Targeting ELF5 and SP1 - Huang, Yulang; Chen, Lifang; Feng, Zongming; Chen, Weixin; Yan, Shaodi; Yang, Rongfeng; Xiao, Jian; Gao, Jiajia; Zhang, Debao; Ke, Xiao (Frontiers in Cell and Developmental Biology, 2021)
Myocardial infarction (MI) remains a leading cause of morbidity and mortality worldwide. Endothelial progenitor cell (EPC)-derived exosomes have been found to be effective in alleviating MI; while the detailed mechanisms remain unclear. The present study aimed to determine the protective effects of EPC-derived exosomal miR-1246 and miR-1290 on MI-induced injury and to explore the underlying molecular mechanisms. The exosomes were extracted from EPCs; gene expression levels were determined by qRT PCR; protein expression levels were determined by western blot and immunofluorescence staining. The angiogenesis and proliferation of human cardiac fibroblasts (HCFs) were determined by tube formation assay and immunofluorescence staining of PKH67, respectively. Luciferase reporter, CHIP and EMSA assays determined the interaction between miR-1246/1290 and the targeted genes (EFL5 and SP1). The protective effects of miR-1246/1290 on MI were evaluated in a rat model of MI. EPC-derived exosomes significantly up-regulated miR-1246 and miR-1290 expression, promoted phenotypic changes of fibroblasts to endothelial cells, angiogenesis and proliferation in HCFs. Exosomes from EPCs with miR-1246 or miR-1290 mimics transfection promoted phenotypic changes of fibroblasts to endothelial cells and angiogenesis in HCFs; while exosomes from EPCs with miR-1246 or miR-1290 knockdown showed opposite effects in HCFs. MiR-1246 and miR-1290 from EPC-derived exosomes induced up-regulation of ELF5 and SP1 respectively by targeting the promoter regions of corresponding genes. Overexpression of ELF5 and SP1 both enhanced phenotypic changes of fibroblasts to endothelial cells and angiogenesis in HCFs pretreated with exosomes from EPCs with miR-1246 or miR-1290 mimics transfection; while knockdown of EFL5 and SP1 exerted opposite effects in HCFs. ELF5 and SP1 can bind to the promoter of CD31, leading to the up-regulation of CD31 in HCFs. Furthermore, in vivo animal studies showed that exosomes from EPCs with miR-1246 or miR-1290 overexpression attenuated the MI-induced cardiac injury in the rats, and caused an increase in ELF5, SP1 and CD31 expression, respectively, but suppressed α-SMA expression in the cardiac tissues. In conclusion, our study revealed that miR-1246 and miR-1290 in EPC-derived exosomes enhanced in vitro and in vivo angiogenesis in MI, and these improvements may be associated with amelioration of cardiac injury and cardiac fibrosis after MI.